Changes and determinants of pneumococcal vaccine uptake in Ethiopia. - Biniyam Tedla Mamo; Ferehiwot Gebrehiwot Geram; Kebron Yihenew Getnet; Zelalem Tazu Bonger (PLOS Global Public Health)
Pneumococcal pneumonia is one of the most common causes of severe pneumonia and pneumonia-related mortality globally. It ranked among the leading causes of morbidity and mortality in children under five years in Ethiopia. Vaccination reduces the burden of pneumonia and pneumococcal infections in both children and adults. This study assesses changes in pneumococcal vaccine coverage over time and identifies factors associated with the vaccine uptake. The study was based on secondary data from the Ethiopian Demographic and Health Surveys (EDHS) in 2016 and 2019, involving 1,929 children in 2016 and 1,008 in 2019, aged 12-23 months. A cross-sectional study design was conducted. The percentage change in pneumococcal conjugate vaccine (PCV) coverage was used to quantify the degree of change over time, while multilevel ordinal logistic regression identifies significant factors. All statistical tests were performed using a 5% significance threshold. The study found a significant 21.8% (95% CI: 9.8-35.2) change in the proportion of children receiving complete doses of PCV, from 49.1% in 2016 to 59.8% in 2019. Children in rural areas were 69% less likely to receive more doses of PCV vaccinations than those living in urban areas (AOR = 0.307, 95% CI: 0.127 - 0.742). Second or higher-order births were associated with greater uptake doses of PCV (AOR = 2.519, 95% CI: 1.143-5.548). Child born in health facilities were 2.35 times more likely to receive full vaccination than those born at home (AOR = 2.350, 95% CI: 1.132-4.882). Additionally, children whose mothers had more antenatal care (ANC) visits were more likely to complete their pneumococcal vaccination. Despite the increase in uptake, Ethiopia remains far from reaching its immunization goals. The study showed that place of residence, birth order, place of delivery, antenatal care and regional variation were significantly associated with pneumococcal vaccine uptake.